Crude toxin of Aggregatibacter actinomycetemcomitans serotype-B increase PARP-1 expression in gingival epithelium - Ernie Maduratna Setiawatie (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2012)
Background: Aggregatibacter actinomycetemcomitans (A. actinomycetemcomitants) serotype-B has long been associated with aggressive periodontitis. Gingival epithelial cell is exquisitely sensitive to the toxin so that may lead to disruption of the epithelial protective barrier, facilitating invasion and perturbation of the underlying connective tissue. Currently suggested that Aa serotypeB produce protein toxin that caused DNA strand breaks. PARP-1 is an abundant nuclear protein functioning as a DNA nick-sensor enzyme. PARP-1 was one of the first identified substrates of caspases, the main executioners of apoptosis. Therefore, a role for PARP-1 in the regulation of apoptosis has been suggested. Purpose: The purpose of this study was to prove PARP-1 expression in gingival epithelium caused by toxin exposure of A. actinomycetemcomitant serotype-B. Methods: This is an experimental study involving twenty adult mice strain Swiss Webster (balb C) divided randomly into two groups: control group (Group A) and toxin group (Group B). Both group were acclimated for one week before treatment. Group A was applied topically with sterile distillated water every 12 hours. Group B was applied topically by 100μg/ml of crude toxin A. actinomycetemcomitant serotype B at the buccal area of mandibular anterior teeth using Hamilton syringe. The mice were sacrificed at 24 hours after toxin application, and then the tissue sections of gingival epithelium were stained with immunohistochemistry to reveal the PARP-1 expression. The data were analyzed with t-test. Results: The PARP-1 expression exhibited an increase with the toxin group (mean= 48.9; SD= 2.01) compared with the control group (mean= 25.21; SD= 1.72). DNA fragmentation appeared from the agarose gel examination, marked as DNA laddering, indicate the cell apoptosis. Conclusion: In conclusion the crude toxin exposure of A. actinomycetemcomitant serotype-B leads to DNA fragmentation and increase PARP-1 expression.Latar belakang: Aggregatibacteractinomycetemcomitans (A. actinomycetemcomitant) serotype-B merupakan etiologi utama periodontitis agresif. Sel epitel gingiva sangat sensitif terhadap toksin sehingga dapat mengganggu epitel sebagai pertahanan awal gingiva, membantu invasi toksin dan mengganggu jaringan ikat dibawahnya. Saat ini diketahui bahwa toksin bakteri Aa serotype-B menyebabkan putusnya rantai DNA. PARP-1 merupakan protein dalam intisel yang berfungsi sebagai DNA nicksensor enzyme. PARP-1 merupakan penanda awal apoptosis, sehingga peran PARP-1 dalam pengaturan apoptosis perlu diteliti Tujuan: Tujuan dari penelitian ini adalah untuk meneliti ekspresi PARP-1 pada epitel gingiva yang dipapar toksin bakteri A. actinomycetemcomitant serotype-B. Metode: Penelitian eksperimen pada 20 mencit strain Swiss Webster (balb C) dibagi secara random dalam 2 kelompok, kelompok kontrol (Group A) dan kelompok perlakuan (Group B). Kedua kelompok diaklimasi sebelumnya selama 1 minggu. Kelompok diaplikasi secara topikal dengan air destilasi steril setiap 12 jam. Kelompok B diaplikasi 100 μg/ml toksin A. actinomycetemcomitant serotype-B secara topikal dengan menggunakan Hamilton syringe. Mencit dimatikan 24 jam setelah aplikasi toksin kemudian potongan epitel gingiva dilakukan pemeriksaan secara imunohistokimia untuk melihat ekspresi PARP-1. Data dianalisis dengan uji-t. Hasil: Ekspresi PARP-1 menunjukkan penigkatan pada kelompok perlakuan (Mean = 48,9; SD = 2,01) bila dibanding kelopok kontrol (Mean= 25,21; SD= 1,72). Tampak adanya gambaran DNA fragmentasi pada pemeriksaan gel elektroforesis yang menunjukkan adanya apoptosis. Kesimpulan: Dapat disimpulkan bahwa paparan toksin A. actinomycetemcomitant serotype-B menyebabkan DNA fragmentasi, dan meningkatkan ekspresi PARP-1.